Developing a mitigation board game integrating animal and plant behavioral indicators to foster problem-solving skills - Agung Wibowo; Evi Fitriana; Dinar Arsy Anggarani; Ajeng Daniarsih; Moch Dicky Novaldi; Halimatus Sa'diyah; Noviansyah Kusmahardhika (Universitas Muhammadiyah Malang, 2026)
Background-Problem-solving skill is one of the essential 21st-century competencies that should be enhanced through contextual learning. Disaster mitigation learning in schools generally remains theoretical and has not fully encouraged students’ active participation in developing higher-order thinking skills. Objectives-This study is aim to develop a disaster mitigation board game integrating animal and plant behavioral indicators to examine its validity, practicality, and effectiveness in enhancing students’ problem solving skills. Method-This research and development employed the ADDIE model, consist of analyze, design, development, implement, and evaluate. The research subjects were 21 students of tenth-grade high school. Data were collected through media and material expert validation sheets, student response questionnaire, and problem-solving skill tests. Data were analyzed using descriptive quantitative analysis, N-Gain calculation, and paired sample t-test. Results-The validation results showed that the media obtained a score of 95% from media experts and 97% from material experts, categorized as very valid. Student responses indicated a practicality level of 92.33% categorized as very practical. The N-Gain value of 0.704 was classified as high effectiveness, and the paired sample t-test results revealed a significant improvement in students’ problem-solving skills (0.00, p<0.05) and Cohen’s d 2.65. Conclusions-The disaster mitigation board game indicated potential effectiveness in improving students’ understanding of adaptive behavior in living organisms within disaster context, as well as fostering critical and collaborative thinking skill. Further research is suggested to use massive field trial thus develop digital version to increase interactivity and accessibility.